Effects of dispersion and fixation of collagen fiber network on its flame retardancy. (May 2020) - Wen, Qilin; Wu, Xintao; Xu, Weixing; Shi, Bi
Abstract: Collagen fiber network (CFN) is a kind of supermolecule composed of collagen molecules with a hierarchical structure. As collagen fibers possess this kind of structure and a relatively high nitrogen content, they have the potential to be processed into an efficacious flame-retardant filler. To realize this potential, the dispersion and fixation of collagen fibers must be controlled effectively. In this study, a series of CFNs with collagen fiber dispersed to different extents and those fixed with different tanning agents were prepared. The fiber dispersion, limiting oxygen index (LOI), combustion performance, thermal stability, carbon residue morphology, carbon residue composition, and thermal conductivity of these CFNs were characterized. The results showed that the flame retardancy of the CFNs improved with an increase in dispersion extent of collagen fibers and removal of the interfibrillar substance. The CFN fixed with 4 wt% zirconium tanning agent (based on ZrO2 ) showed the best flame-retardant performance. Its LOI, total heat release, char yield at 800 °C and thermal conductivity were 62.3%, 15.51 MJ m −2, 18.33%, and 0.1362 W m −1 K −1, respectively. Because of these properties, this Zr-loaded CFN can be considered as a valuable flame retardant modifier for polymer materials. Graphical abstract: Image 1 Highlights: The novel flame retardance material based on collagen fiber network. The strategy for control the structure and property of collagen fiber network. A novel way to utilize collagen fiber material.